QARAQALPAQ BAQSÍ – JÍRAWLARÍNÍŃ TARIYXÍY DÓRETIWShILIK ÓNERLERI MENEN TANÍSTÍRÍW USÍLLARÍ - Axetova, G.J. (SCIENCE and SOCIETY, 2023)
This article talks about using interactive methods in music lessons. The concepts of storytellers and the epic are considered. The rules are noted for executing methods.
Keywords: интерактивные методы; музыка; сказители; эпос; қобыз; дутар